Protective properties of kefir on burn wounds of mice that were infected with S. aureus, P. auroginasa and E. coli - Cetik Yildiz, Songul; Demir, Cemil; Cengiz, Mustafa; Ayhanci, Adnan (Cellular and Molecular Biology, 2019)
Burns and burn wounds are very sensitive to infections and cause a large amount of death worldwide. Although burn wound is sterile at the beginning, because of the risk factors such as prolonged hospital stay, immune suppression and burn affecting large surface area, colonisation with Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli occur. For the burn therapy, one of the most important ways is to control bacterial infections. A probiotic fermented milk product kefir has antioxidant, antimicrobial, antiinflammatory, anticancer and various health promoting features. This study aims to examine possible protective properties of kefir which was used on the burn wounds that were infected with S. aureus, P. auroginasa and E. coli. Swiss albino / Balb-c mice were seperated into four groups: (1) used as control group, (2) second-degree burn model+ burn wounds were infected with P.aeruginosa + S.aureus + E.coli, (3) second-burn wounds were treated with sterile pads dressed with kefir and (4) second-degree burn+burn wounds were infected with P. aeruginosa + S.aureus +E.coli before being treated with sterile pads dressed with kefir. The serum biochemical results verified the histopathological results and our findings showed that kefir is an effective product with cell-protecting properties.